Photo‐mediated ultrasound therapy for the treatment of retinal neovascularization in rabbit eyes. Issue 5 (23rd March 2022) - Qin, Yu; Yu, Yixin; Fu, Julia; Wang, Mingyang; Yang, Xinmai; Wang, Xueding; Paulus, Yannis M.
Abstract: Objectives: Retinal neovascularization (RNV) is the growth of abnormal microvessels on the retinal surface and into the vitreous, which can lead to severe vision loss. By combining relatively low‐intensity ultrasound and nanosecond‐pulse‐duration laser, we developed a novel treatment method, namely photo‐mediated ultrasound therapy (PUT), which holds a potential to remove RNV with minimal or no damage to the adjacent tissues. Methods: RNV was created in both albino and pigmented rabbits ( n  = 10) through a single intravitreal injection with DL‐α‐aminoadipic acid. RNV was treated with PUT 8 weeks postinjection. After PUT treatment, animals were evaluated longitudinally for up to 6 weeks. Treatment outcomes were evaluated through fundus photography, red‐free fundus photography, fluorescein angiography (FA), and histopathology. Results: In both albino and pigmented rabbits, there were no leakage in the treatment area immediately after PUT treatment as demonstrated by FA, indicating the cessation of blood perfusion of the RNV in the treated area. The fluorescence leakage did not recover in albino rabbits during the 6‐week posttreatment monitoring period, and only 9.9 ± 9.8% of the neovascularization remained at the end of 6 weeks. In the pigmented rabbits, the fluorescence leakage partially returned, but the level of leakage decreased over time during the 6‐week posttreatment monitoring period, and only 10.8 ± 9.8% of the neovascularization remained at the end of 6 weeks. Histology demonstrated removal of vasculature without damage to the surrounding neurosensory retina. Conclusions: These results demonstrate that PUT could precisely remove RNV without damage to the surrounding neurosensory retina in both rabbit strains.